Experimental Investigation of the Effects of a Blood Stopper Agent (Ankaferd Blood Stopper) on Bone Surfaces - Şimşek, Hasan Onur (Galenos Publishing, 2013)
Objective: This study aims to experimentally investigate the efficiency of Ankaferd Blood Stopper (ABS) on early and long-term bone healing and its effects on bone surfaces. Materials and Methods: Thirty adult male Wistar albino rats were used in the study. These rats were randomly divided into three groups, and bilaterally bone defects were created in the femur of each rat. A 3.0-mm-deep monocortical circular defect was created with a 3.0 mm diameter trephine drill on the proximal part of the femur, and 0.05 mL ABS was applied to the experimental group while the control group was left untreated. Group 1, group 2, and group 3 rats were sacrificed on days 7, 28, and 42, respectively. Trabecular bone area (Tb.Ar), medullary bone diameter (Me.Dm), osteoblast area (Ob.Ar), osteoid area (O.Ar) and mineralized bone area (Md.Ar) were examined in the histomorphometric analysis. Also new bone formation was scored according to the histologic evaluation Results: The results showed that while new the to day 7 experimental group showed much more bone formation than the to day 7 control group, there was no significant difference between the to day 28 and day 42 experimental groups and to day 28 and day 42 control groups. Accordingly, ABS applied in bone cavities only had a larger accelerator effect on bone healing for the seventh-day to day 7 experimental group. In clinical observations, no allergic or inflammatory reactions were observed on the skin and other preoperative and postoperative periods. Moreover in, the histomorphometric study, necrotic areas and infection areas were not observed. Conclusion: ABS has an acceleratory effect on the short-term bone healing process and is a reliable agent for routine use. However, its effects on the long-term bone healing process are insignificant. We think that a wide series of research projects are required to confirm the effects of ABS speeding up the healing process in addition to its characteristic as a blood stopping agent. Conflict of interest:None declared.